Data clustering using maximum dependency of attributes and its application to cluster agricultural products - Hafiz Kamal, Leang (2012)
This project is about understanding the method of Clustering Data using Rough set Theory.The technique used is Maximum Dependency of attributes.The way this technique work is by calculating the degree of each attribute and selecting the highest dependency based on the degree. The highest degree of attribute will be chosen as the best attribute to be used to cluster the data.A system will be built by using Visual Basic (VB)that will implement this technique to cluster large data faster and easier.